Evaluation of the knowledge about ora-pro-nóbis from the perspective of the use of the stories tool in the social network Instagram (Research, Society and Development, 2021)
The knowledge on the diversity of Brazilian flora and its nutritional potential, especially regarding Unconventional Food Plants (UFPs), is important in order to expand the options of healthy foods for a continuously growing population. Among the UFPs native to Brazil, ora-pro-nóbis (OPN) has been gaining ground in scientific research and in the consumer market due to its nutritional and functional potential. Givento its public reach, the use of social networks such as Instagram is relevant for assessing markets, publicizing, popularizing and elucidating. For instance, regarding the safety of in consuming new products. This study used the Instagram Stories tool to assess Instagram users' knowledge on UFPs and, more specifically, on OPN. A total of 10 questions (objective and discursive) were posted on Instagram Stories over the course of 24 hours. Data was analyzed according to audience engagement and in relation to the simple and relative frequency of responses. The highest engagements obtained were in the question about consumption (27.20%) and knowledge (26.67%) of OPN. The highest frequency of positive answers (87.56%) was obtained in the question that asked whether the individual would consume OPN-derived products and the highest frequency of negative answers (84.81%) was obtained in the question about the use of UFP in food. The reached audience demonstrated knowledge and previous experience in consuming OPN leaves, and its protein potential was considered the most attractive feature of this type of food. Despite the little use of UFPs in food, the consulted public showed interest in consuming flour and other OPN-derived products.